The human rights of migrants in Angola: two years after the visit of the UN special envoy - Chico, Avelino (2018)
There is growing interest in the human right of migrants in Angola. Not long ago, Angolans used to leave their country because of the war. Nevertheless, since the end of the conflict, in 2002, the country has seen the flows of immigrants and refugees. Political stability and economic growth are among the pull factors. Even the economic crisis, which is actually affecting the country, has stopped the flows of migrants. For this reason, François Crépeau, the UN special rapporteur on the human rights of migrants, visited the country. At the end of his stay, he wrote a report on the human rights of migrants. This article intends to analyze it and emphasize that, two years after his visit, the situation remains the same